A voyage from the ER: spatiotemporal insights into polarized protein secretion in neurons - Kersten, Noortje; Farías, Ginny G. (Frontiers in Cell and Developmental Biology, 2023)
To function properly, neurons must maintain a proteome that differs in their somatodendritic and axonal domain. This requires the polarized sorting of newly synthesized secretory and transmembrane proteins into different vesicle populations as they traverse the secretory pathway. Although the trans-Golgi-network is generally considered to be the main sorting hub, this sorting process may already begin at the ER and continue through the Golgi cisternae. At each step in the sorting process, specificity is conferred by adaptors, GTPases, tethers, and SNAREs. Besides this, local synthesis and unconventional protein secretion may contribute to the polarized proteome to enable rapid responses to stimuli. For some transmembrane proteins, some of the steps in the sorting process are well-studied. These will be highlighted here. The universal rules that govern polarized protein sorting remain unresolved, therefore we emphasize the need to approach this problem in an unbiased, top-down manner. Unraveling these rules will contribute to our understanding of neuronal development and function in health and disease.